Barriers to research in interventional radiology within the UK. Issue 12 (December 2022) - Jenkins, P.; MacCormick, A.; Harborne, K.; Liu, W.; Mahay, U.; Zhong, J.; Haslam, P.
Abstract : Aim: To identify these barriers to research within interventional radiology (IR) and suggest potential solutions to support IR academia within the UK and beyond. Materials and methods: An electronic survey was compiled using Google Forms and distributed to the British Society of Interventional Radiology (BSIR) members by email and through social media (Twitter). The survey was open between 15 October 2021 and 15 December 2021. Questions included prior research experience and qualifications, research interests and barriers to research development. The data were analysed in Microsoft Excel 365. Results: One hundred and six responses were received with the majority from junior (42.5%) and senior radiology trainees (25.5%). Eight-three percent had not undertaken formal research qualifications with 56.4% stating they would like to undertake a PhD or MD; 81.1% stated they planned to be involved in research. The most common perceived barriers were lack of time (64.2%), lack of research experience (61.3%), and lack of senior supervision (58.5%). Conclusion: Developing and supporting the academic IR infrastructure is vital to ensure the future of IR. Radiology trainees have shown interest in being involved with IR research and undertaking formal research training. Additional support from local hospitals, national societies, and the Royal College of Radiologists are required. Highlights: Significant enthusiasm amongst IR trainees to get involved in clinical research. There are numerous that may prohibit this research involvement. Key action points in order increase the accessibility to research in IR.